2021
DOI: 10.1038/s41598-021-01809-y
|View full text |Cite|
|
Sign up to set email alerts
|

The evolutionary conserved TLDc domain defines a new class of (H+)V-ATPase interacting proteins

Abstract: We recently found that nuclear receptor coactivator 7 (Ncoa7) and Oxr1 interact with the proton-pumping V-ATPase. Ncoa7 and Oxr1 belong to a group of proteins playing a role in the oxidative stress response, that contain the conserved “TLDc” domain. Here we asked if the three other proteins in this family, i.e., Tbc1d24, Tldc1 and Tldc2 also interact with the V-ATPase and if the TLDc domains are involved in all these interactions. By co-immunoprecipitation, endogenous kidney Tbc1d24 (and Ncoa7 and Oxr1) and ov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 42 publications
(60 reference statements)
1
25
0
Order By: Relevance
“…Second, homologs of Red contain a LysM domain, and it is their only annotated feature (Francescutti et al, 2022; Grant et al, 2016). The molecular function of this domain is poorly understood in insects, but there is mounting evidence in vertebrates that the LysM domains of several genes interact with the v-ATPase to modulate vacuolar pH across a variety of endosomal organelles (Merkulova et al, 2015; Castroflorio et al, 2021; Eaton et al, 2021; Tan et al, 2022). There is precedent for a role of pterinosome acidification in modulating the red vs. yellow states of squamate pigment cells (Saenko et al, 2013), and the roles of melanosomal pH and v-ATPase activity in fine-tuning melanin content are well established in vertebrates (Ramos-Balderas et al, 2013; Wakamatsu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Second, homologs of Red contain a LysM domain, and it is their only annotated feature (Francescutti et al, 2022; Grant et al, 2016). The molecular function of this domain is poorly understood in insects, but there is mounting evidence in vertebrates that the LysM domains of several genes interact with the v-ATPase to modulate vacuolar pH across a variety of endosomal organelles (Merkulova et al, 2015; Castroflorio et al, 2021; Eaton et al, 2021; Tan et al, 2022). There is precedent for a role of pterinosome acidification in modulating the red vs. yellow states of squamate pigment cells (Saenko et al, 2013), and the roles of melanosomal pH and v-ATPase activity in fine-tuning melanin content are well established in vertebrates (Ramos-Balderas et al, 2013; Wakamatsu et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This variability between the binding mode and effect of TLDc proteins points to interesting differences throughout the TLDc protein family, which have been linked to numerous different processes ( Finelli et al, 2019 ; Svistunova et al, 2019 ; Castroflorio et al, 2021 ). Although it has become clear that TLDc domains are V-ATPase interaction modules ( Eaton et al, 2021a ), the differences between the proteins suggests a fascinating diversity of biological roles that remains to be uncovered.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of V-ATPase from kidney tissue identified ARHGEF7, DMXL1, EZR, NCOA7, OXR1, RPS6KA3, SNX27, and nine subunits of the CCT complex as V-ATPase associated proteins ( Merkulova et al, 2015 ). Two of these proteins, NCOA7 and OXR1, contain TLDc domains (Tre2/Bub2/Cdc16 lysin motif domain catalytic), which has been proposed as a V-ATPase interacting module ( Eaton et al, 2021a ). These proteins are believed to protect against oxidative stress through an unknown mechanism ( Finelli et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…[ 35 ] More recently, a direct interaction was observed between the V‐ATPase and mammalian NCOA7, OXR1, TBC1D24, mEAK7, and TLDC2. [ 36 ] Further, mEAK7 has been identified in V‐ATPase preparations from human cells [ 38,86 ] and pig kidney. [ 39 ] The accompanying cryoEM structures showed the enzymes halted in rotary state 2, with mEAK7 bound to the C‐terminal domains of the non‐catalytic subunit AB pair located behind peripheral stator EG3 (Figure 5B).…”
Section: Introductionmentioning
confidence: 99%
“…[ 38 ] As mentioned, a recent study showed that five mammalian TLDc family members were able to co‐immunoprecipitate with the V‐ATPase. [ 36 ] Thus, the TLDc domain can be classified as a V‐ATPase interaction module, with the various N‐ or C‐terminal extensions likely mediating different effects on enzyme function that favor similar but distinct binding sites on the enzyme, as seen for mEAK7.…”
Section: Introductionmentioning
confidence: 99%